HUMAN INFECTION WITH ISOSPORA HOMINIS.A CASE REPORT - M.Rezaian M.Ghorbani (Tehran University of Medical Sciences, 1985)
A case of Isospora hominis infection was revealed by stool examination using formol- ether concentration technique. The patient was a 26 year-old female from rural area of Babol, Caspian Sea littoral, with complaints of abdominal discomfort.